Revision of the Malagasy ponerine ants of the genus Leptogenys Roger (Hymenoptera: Formicidae) - Rakotonirina, Jean Claude; Fisher, Brian L. (Zootaxa, 2014)
Leptogenys is the most diverse ponerine ant genus in the world; it is widespread throughout tropical and subtropical regions and there are over 200 extant species described. Most species have ergatoid queens, and many have falcate, bowed mandibles and are specialists on isopod prey. Here, the Malagasy Leptogenys are revised with 60 species recognized, of which 40 are newly described, 18 redescribed, and two subspecies raised to species rank and redescribed. Included in the revision are a key to species based on the worker caste, geographic distributions, descriptions of intraspecific variation, and notes on natural history. The following species are redescribed: L. acutirostris Santschi, L. alluaudi Emery, L. angusta (Forel), L. antongilensis Emery, L. arcirostris Santschi, L. coerulescens Emery, L. falcigera Roger, L. gracilis Emery, L. grandidieri Forel, L. incisa Forel, L. maxillosa (F. Smith), L. oswaldi Forel, L. pavesii Emery, L. ridens Forel, L. saussurei (Forel), L. stuhlmanni Mayr, L. truncatirostris Forel, and L. voeltzkowi Forel. The following are raised to species and redescribed: L. imerinensis Forel stat. rev., stat. n.; and L. suarensis Emery stat. rev., stat. n. The following are described as new: L. alamando sp. n., L. alatapia sp. n., L. ambo sp. n., L. andritantely sp. n., L. anjara sp. n., L. avaratra sp. n., L. avo sp. n., L. barimaso sp. n., L. bezanozano sp. n., L. borivava sp. n., L. chrislaini sp. n., L. comajojo sp. n., L. diana sp. n., L. edsoni sp. n., L. fasika sp. n., L. fiandry sp. n., L. fotsivava sp. n., L. johary sp. n., L. lavavava sp. n., L. lohahela sp. n., L. lucida sp. n., L. malama sp. n., L. mangabe sp. n., L. manja sp. n., L. manongarivo sp. n., L. mayotte sp. n., L. namana sp. n., L. namoroka sp. n., L. pilaka sp. n., L. rabebe sp. n., L. rabesoni sp. n., L. ralipra sp. n., L. sahamalaza sp. n., L. tatsimo sp. n., L. toeraniva sp. n., L. tsingy sp. n., L. variabilis sp. n., L.vatovavy sp. n., L. vitsy sp. n., and L. zohy sp. n. Most of these species are endemic to the region. Of the endemic species, two are restricted to the Comoros (L. comajojo, L. mayotte), 52 occur only in Madagascar, and two are shared by both islands (L. fiandry, L. gracilis). Three species in the maxillosa group, considered introduced to the region, are recorded from Madagascar, Comoros, Mauritius, Reunion, and Seychelles. Leptogenys stuhlmanni, the only species in the stuhlmanni group, which was collected and first described from Moheli by Forel in 1907, has not been rediscovered and may have gone locally extinct.